THE REFORMULATION MARKER OF EXPLANATION <ES DECIR> IN CHILEAN SPANISH: A PROPOSAL FOR FUNCTIONAL CLASSIFICATION - Castillo Fadic, María Natalia; Sologuren Insua, Enrique (Lenguas Modernas, 2018)
The present study analyzes the functions of the reformulation marker of explanation <es decir> used in Chilean Spanish. This marker was observed in the Corpus Básico del Español de Chile, which contains 500.000 words distributed in 5 worlds: Drama, Narration, Essay, Scientific-technical texts and Press. In this corpus, 81% of the entries are found in Essay and Scientific-technical texts, showing its relevance in academic writing (Núñez, Muñoz y Mihovilovic, 2006). The theoretical-methodological perspective on which this analytical-descriptive construct is based, considers the contributions of textual (Ciapuscio, 2001), pragmatic (Portolés, 2007) and declarative approaches (García Negroni, 2009) to the study of discourse markers. A qualitative-quantitative methodology is used due to the need of corpus studies on which it is possible to see how markers work in written texts in Chilean Spanish. The main results reveal a specialized marker, as well as different micro and macro functions shown at a lexical and discursive level. Finally, a classification model of the functions intra sentence for the reformulation marker of explanation <es decir> is proposed which can be applied to different oral and written corpuses in order to refine the taxonomy and to contribute to the description of this marker in the Chilean variant of Spanish language.